Dampak Buruk Polusi Udara Bagi Kesehatan Dan Cara Meminimalkan Risikonya - Shinta Maharani; Wayan Redi Aryanta (Jurnal Ecocentrism, 2023)
This literature review aims to determine the types of pollutants in the air, the range of air quality, the effects of air pollution, the adverse effects of air pollution on health and efforts to minimize the risks. The results of a literature search show that the types of pollutants that pollute the air are particulate matter, ozone, nitrogen dioxide, sulfur dioxide, carbon monoxide, viruses, fungi and bacteria. The range of air quality based on the air quality index is 0-50: healthy, 51-100: moderate, 101-150: unhealthy for sensitive individuals, 151-200: unhealthy for all groups, 201- 300: very unhealthy, 301 -500: dangerous. The effects of air pollution on health are fast and slow depending on individual sensitivity. The adverse effects of air pollution on health are triggering asthma attacks, triggering lung cancer, increasing the risk of infection and inflammation in the lung tissue, inhibiting child development, increasing the risk of low birth weight, causing respiratory problems, causing other lung diseases, increasing the risk heart disease and stroke, increase the risk of death, and interfere with mental health. Ways to minimize the adverse effects of air pollution on health, starting from yourself and the environment, are reducing the use of motorized vehicles, reducing the use of fossil fuels for energy production, buying recycled products, using sustainable products, planting trees, walking, riding bicycles, using public transportation, eating local and organic products, eating less meat, gardening, increasing awareness of the environment, and not using plastic bags. Another way is to consume food that is rich in essential nutrients and contains various antioxidants such as food sources of vitamin C, vitamin E, beta carotene and omega-3. When air pollution increases, foods that are suitable for consumption are broccoli, avocados, olive oil, nuts, oranges, grapes, turmeric, spinach, flaxseeds, and foods that are rich in vitamin B6, vitamin B12 and methionine which are sourced from natural ingredients. vegetable food, as well as animal food sources of omega-3 such as milk, cheese and fish. In addition, it is also necessary to apply a good lifestyle, a positive mindset and a healthy diet. Keywords : air pollution, health, disease, environment, food.